Overview of the Atmospheric Brown Cloud East Asian Regional Experiment 2005 and a study of the aerosol direct radiative forcing in east Asia - Nakajima, T; Yoon, S; Ramanathan, V; Shi, G; Takemura, T; Higurashi, A; Takamura, T; Aoki, K; Sohn, B; Kim, S; Tsuruta, H; Sugimoto, N; et al. (2007)
This article introduces an international regional experiment, East Asian Regional Experiment 2005 (EAREX 2005), carried out in March-April 2005 in the east Asian region, as one of the first phase regional experiments under the UNEP Atmospheric Brown Cloud (ABC) project, and discusses some outstanding features of aerosol characteristics and its direct radiative forcing in the east Asian region, with some comparison with the results obtained in another ABC early phase regional experiment, ABC Maldives Monsoon Experiment (APMEX) conducted in the south Asian region. Time series of aerosol optical thickness (AOT), single scattering albedo (SSA), aerosol extinction cross section profile and CO concentration shows that air pollutants and mineral dust were transported every 5 to 7 days in the EAREX region to produce SSA values at wavelength of 700 nm from 0.86 to 0.96 and large clear-sky shortwave forcing efficiency at 500 nm from 60 W m-2 to go W m-2, though there are some unexplained inconsistencies depending on the evaluation method. The simulated whole-sky total forcing in the EAREX region is -1 to - 2 W m-2 at TOA and -2 to -10 W m-2 at surface in March 2005 which is smaller in magnitude than in the APMEX region, mainly because of large cloud fraction in this region (0.70 at Gosan versus 0.51 at Hanimadhoo in the ISCCP total cloud fraction). We suggest there may be an underestimation of the forcing due to overestimation of the simulated cloudiness and aerosol scale height. On the other hand, the possible error in the simulated surface albedo may cause an overestimation of the magnitude of the forcing over the land area. We also propose simple formulae for shortwave radiative forcing to understand the role of aerosol parameters and surface condition to determine the aerosol forcing. Such simple formulae are useful to check the consistency among the observed quantities. Copyright 2007 by the American Geophysical Union.